2016
DOI: 10.1128/jb.00596-15
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Limitation, BvgAS Activation, and (p)ppGpp Regulate the Expression of the Bordetella pertussis Type 3 Secretion System

Abstract: Bordetella pertussis is a bacterium that is considered to be highly adapted to humans, and it has not been isolated from the environment. As this bacterium does not utilize sugars, the abundant supply of glutamate in Stainer Scholte (SS) medium enables B. pertussis to grow efficiently in liquid culture in vitro, and as such, SS medium is a popular choice for laboratory experiments. However, the concentration of glutamate in the in vivo niche of B. pertussis is quite low. We investigated the bacterial response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Down-regulation of the T3SS genes, accompanied by attenuated virulence and reduced growth, was also reported in the P. syringae (p) ppGpp 0 mutants [16]. Similar results were also reported in Bordetella pertussis in response to glutamine limitation [29] and in E. coli in response to nutrient starvation [15]. Previous studies have demonstrated that the T3SS gene expression in E. amylovora reached the highest level at 6 hpi in HMM [23].…”
Section: Positive Regulation Of Virulence-related Genes By (P) Ppgppsupporting
confidence: 80%
“…Down-regulation of the T3SS genes, accompanied by attenuated virulence and reduced growth, was also reported in the P. syringae (p) ppGpp 0 mutants [16]. Similar results were also reported in Bordetella pertussis in response to glutamine limitation [29] and in E. coli in response to nutrient starvation [15]. Previous studies have demonstrated that the T3SS gene expression in E. amylovora reached the highest level at 6 hpi in HMM [23].…”
Section: Positive Regulation Of Virulence-related Genes By (P) Ppgppsupporting
confidence: 80%
“…Upregulation of BP3831 may lead to greater acquisition of glutamate where it is limited in the respiratory tract, therefore enhancing metabolic efficiency and fitness. It has also been found that low levels of glutamate leads to higher expression of the T3SS, therefore decreased T3SS expression in L1423 may also be linked to greater acquisition of glutamate.…”
Section: Discussionmentioning
confidence: 96%
“…However, the importance of the T3SS in B. pertussis has not been clear. Although some previous work had failed to detect T3SS proteins in B. pertussis and concluded that the T3SS may be inactive (46), other work has challenged this idea by demonstrating that clinical isolates and laboratory-adapted B. pertussis strains under certain nutrition-limited cultures produce T3SS proteins (50). In addition, Ahuja et al (32) recently reported that in both B. pertussis and B. bronchiseptica, BtrA (BP2233) functions as an anti-sigma factor for BrpL, the ECF sigma factor responsible for T3SS expression.…”
Section: Figmentioning
confidence: 92%